Sosialisasi dan Pendampingan Digital Marketing di Era Pandemi Covid 19 Pada Kelompok Wanita Tani Kelurahan Tembong Kota Serang - Endang Tri Santi; Marthalena; Eva Fachriyah (BANTENESE : JURNAL PENGABDIAN MASYARAKAT, 2021)
Covid 19 has an impact on the economic decline evenly, one of which is the level of people's purchasing power decreases. Coupled with the existence of social restrictions that do not allow people to interact with each other, it greatly affects sales revenue, especially marketing that still uses and relies on conventional systems. Therefore, there is a need for assistance to do digital marketing, especially in this era of sophisticated technology. Because it is undeniable that online marketing is an alternative, not just to keep up with the times, but also a way to adapt to the pandemic conditions that have not subsided. The purpose of this activity is to conduct socialization and assistance to the community, especially women farmer groups regarding how to make product packaging techniques attractive and marketing techniques through digital, with the hope that people will not only do conventional marketing but also digitally. The method used is by socializing or delivering digital marketing materials and theories, as well as direct practical assistance on how to package products, take product photos, use social media, and so on. From the assistance that has been carried out by women farmer groups, they can apply social media including whatsapp and facebook as a means of making sales so that the products or agricultural products they market more attract the wider community